Compliance with Financial Accounting Standards in Village-Owned Enterprises: An Examination of Financial Report Presentation for Entities without Public Accountability - Winarti, Winarti; Jumriani, Jumriani; Akbardin, Muhammad; Mangga, Andi Rahmatullah; Mauna, Randy (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This research aimed to understand the presentation of financial reports by SAK-ETAP at BUMDes Amanah Lembang Lohe. Research Design and Methodology: The research employed both primary and secondary data sources. Primary data was collected through observations, interviews with authorized parties, and research on the company. Secondary data included published data collectors and a brief company history. Data collection methods included interviews, direct question-and-answer sessions with BUMDes management, and the collection of documents and archives from BUMDes Amanah Lembang Lohe. The analytical method employed was a descriptive qualitative approach. Findings and Discussion: The research findings indicate that the preparation of financial reports by SAK-ETAP at the Amanah Lembang Lohe Village-Owned Enterprise has not been implemented. This is due to several inhibiting factors that make it difficult for managers to present reports by financial accounting standards. Implications: This research provides insights into the challenges faced by BUMDes Amanah Lembang Lohe in presenting financial reports aligned with SAK-ETAP and identifies obstacles that need to be addressed for effective reporting.